2020
DOI: 10.29252/ibj.24.6.381
|View full text |Cite
|
Sign up to set email alerts
|

Status of Biofilm-Forming Genes among Jordanian Nasal Carriers of Methicillin-Sensitive and Methicillin-Resistant Staphylococcus aureus

Abstract: Introduction: Biofilm formation in Staphylococcus aureus is a major virulence factor. Both MSSA and MRSA are common causes of community-and hospital-acquired infections and are associated with biofilm formation. The status of biofilm-forming genes has not been explored in Jordanian nasal carriers of S. aureus. This study investigates antibiotic resistance patterns and the prevalence of biofilm-forming genes between MSSA and MRSA in two distinct populations in Jordan. Methods: A total of 35 MSSA and 22 MRSA iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
2
11
1
Order By: Relevance
“…In addition, we found that most isolates (66.1%, 41/62) were strong biofilm-forming strains. However, the study of Khasawneh et al (2020) showed that the proportions of strong, medium, and weak biofilm forming strains among 57 S. aureus isolates were 12.3, 80.7, and 7.0%, respectively. Triveni et al (2018) reported that only 72 (38.3%) of the 188 strains of S. aureus were screened as biofilm producers, of which 34 (18.1%) were strong biofilm-forming strains and 38 (20.2%) were medium biofilm-forming strains.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we found that most isolates (66.1%, 41/62) were strong biofilm-forming strains. However, the study of Khasawneh et al (2020) showed that the proportions of strong, medium, and weak biofilm forming strains among 57 S. aureus isolates were 12.3, 80.7, and 7.0%, respectively. Triveni et al (2018) reported that only 72 (38.3%) of the 188 strains of S. aureus were screened as biofilm producers, of which 34 (18.1%) were strong biofilm-forming strains and 38 (20.2%) were medium biofilm-forming strains.…”
Section: Discussionmentioning
confidence: 95%
“…Biofilm production is considered to be an important factor in S. aureus pathogenesis, antibiotics resistance, and immune evasion (Khasawneh et al, 2020). Biofilm‐forming S. aureus causes many diseases including endocarditis, septicemia, osteomyelitis, pneumonia, pleuropulmonary and device‐related infections (Lister & Horswill, 2014; Shivaee et al, 2019; Tong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 83 MSSA and 80 MRSA samples isolated from different clinical sources were genetically and phenotypically characterized for biofilm formation. Biofilm production is usually genetically associated with the presence of elements of the ica ABCD operon (Cramton et al, 1999; Khasawneh et al, 2020; Knobloch et al, 2002; Rohde et al, 2001; Shivaee et al, 2019). While many studies have demonstrated ica ADBC frequencies of 77%–100%, most have not found a correlation between the presence of ica elements and biofilm formation phenotype (Cramton et al, 1999; Khasawneh et al, 2020; Knobloch et al, 2002; Rohde et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations